Estimation of Serum Adenosine Deaminase-2 (ADA2) as One of the Non- Invasive Diagnostic Marker of Pleural Effusion in Systemic Lupus Erythromatosus - Syed Amanullah Shah, Abdul Salam, Ishfaq Ahmed, Faheem Ahmed Solangi, Hafiz Abdul Rauf, Zeeshan Ul Haque, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Systemic Lupus Erythromatosus (SLE) is an autoimmune disorder which disturbs the normal life of human due to involvement of different vital organs like bones, lungs, heart & kidney etc. A pleural effusion is one of the most common complications associated with lung involvement in young female patients with SLE. Pleural fluid examination is the main method for diagnosis, but lack of trained people and limited resources necessitate evaluating the non-invasive cheap method. Objective: To estimate the serum ADA2 level as one of non invasive marker for the diagnostic tool of pleural effusion in SLE Methodology: There were 29 female cases of SLE diagnosed in different remote areas of Pakistan divided into two groups: group-I contained 16 diagnosed cases of SLE without pulmonary involvement, and group-II contained 13 diagnosed cases of SLE with pleural effusion. The serum ADA2 level was estimated by using the ELISA method by using sandwich technology in conjunction with the ELISA method. In order to conduct the statistical analysis of the data, SPSS version 22 was used to apply an independent Student t-test. Results: The mean serum ADA2 of group-I was 15.1 ± 2.14 U/L while mean value of serum ADA2 of group-II was 11.13 ± 1.76 U/L. There was statistical (p<0.05) decreased level of serum ADA2 in patients of group-II patients with compared the patients of group-I patients. Conclusion: Serum ADA2 level in the serum may be one of diagnostic marker for the diagnosis of pleural effusion in the patients of SLE